Fatigue after subarachnoid haemorrhage: a study of patients with good clinical outcome - G. Makarevičius; K. Pilypaitė; G. Terbetas; G. Šustickas; G. Bulotienė (Neurologijos seminarai)
Background. Recent studies have shown that the prevalence of fatigue in patients after subarachnoid haemorrhage (SAH) is high. However, data on patients with good clinical outcome are still scarce, since in clinical practice, the condition of patients is usually judged by physical parameters and mental condition is rarely considered. Thus, we aimed to determine the risk factors and prevalence of chronic fatigue among SAH patients in Lithuania. Material and methods. Patients with good clinical outcome (Glasgow outcome scale=5, no major paresis) who were diagnosed with SAH and treated at the Republican Vilnius University Hospital between January 2018 – January 2021 were studied at least 6 months after discharge from the hospital. Patients diagnosed with other medical conditions known to result in chronic fatigue were excluded. To evaluate fatigue symptoms, patients were asked to fill in the Lithuanian version of the Multidimensional Fatigue Inventory (MFI-20L) questionnaire. Analyses were performed using RStudio version 2022.02.1. Results were considered statistically significant at p value <0.05. Results. Total of 30 patients participated in our study: 20 female (66.67%) and 10 male (33.33%), median age 47 years (range 29-68). The median duration between SAH and fatigue evaluation was 37.5 months (range 11-46). Mean MFI-20L scores on fatigue subscales were 0.59±0.27 for general, 0.57±0.27 for physical, 0.55±0.29 for mental fatigue, 0.55±0.29 for reduced activity, and 0.44±0.22 for reduced motivation subscales. There were no statistically significant mean differences of general fatigue score between different age (p=0.64) and sex (p=0.20) groups. Mean general fatigue score between patients who had vasospasm (p=0.21) or any complication (p=0.68) after SAH did not differ statistically significantly from those who had not. Mean general fatigue score was statistically significantly higher in patients with poorer condition on admission (defined as Hunt and Hess grade >2) (p=0.02) and in patients with a longer period after SAH (p=0.02). Conclusions. Fatigue is pronounced in patients who survive SAH. This is most evident in those patients who had poorer clinical condition on admission and worsened over time. General and physical fatigue were the most pronounced types of fatigue in our study group.